Involvement of the Redox System in Chilling Injury and Its Alleviation by 1-Methylcyclopropene in 'Rojo Brillante' Persimmon - Novillo, Pedro; Salvador, Alejandra; Navarro, Pilar; Besada, Cristina (2017)
A treatment with 1-methylcyclopropene (1-MCP) is known to reduce softening to the flesh of ‘Rojo Brillante’ persimmon, which is the main chilling injury (CI) symptom that occurs after storage at low temperature. However, very little is known about the mechanism by which 1-MCP confers persimmon tolerance to chilling. The aim of this study was to investigate the changes in the redox system associated with CI and its reduction by 1-MCP during storage at 1 °C and after shelf life period. Our results showed that during cold store, both control and 1-MCP treated fruit underwent gradual oxidative stress (accumulation of H2O2, increment in APX, CAT, LOX, and slight increase in SOD activity) but no CI was manifested. During shelf life conditions, ethylene production was slightly higher in control than in 1-MCP treated fruit. Besides, the CI manifestation of control fruit was associated with oxidative burst [major H2O2 accumulation and sharp increase in catalase (CAT), peroxidase (POD), and lipoxygenase (LOX) activity], while 1-MCP treatment greatly reduced the CI symptoms. The 1-MCP treated fruit showed down-regulated POD activity and up-regulated CAT activity, which resulted in slower H2O2 accumulation. The reduction of the flesh softening as the main manifestation of CI in ‘Rojo Brillante’ persimmon by 1-MCP was associated with the modulation of the redox state of the fruit during the shelf life period that follows low-temperature storage.